Implementasi Peraturan Tentang Merek Di Kelurahan Sambung Jawa Makassar - Handayani, Dwi (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
Makassar community is divided into sub-district, Â urban village, hamlet, and neighborhood unit with all its issues. One of the problems is in the Sambung Jawa, Mamajang Sub-district where there is still lack of interest and awareness to understand the importance of knowledge about the rights and obligations of a trading business (legal entity). On the other hand, there are some people who have succeeded, but are more concerned with pursuing profits to meet their needs than caring about legal issues. The solution to these problems is providing legal assistance and socialization regarding the establishment of a business entity (formerly home industry) carried out in the communities of RW 6, 7, 8, and 9 who have business activities in clothing, crafts and food industry as UMK (Micro and Small Enterprises) entrepreneurs, procedures and terms of submission of brands, as well as providing information about brand rights.The aim of this activity is to increase legal awareness and provide legal protection by continuous (periodically) mentoring both during service and afterwards. The method that used are direct meeting with servants and local officials / community leaders and discussions with partners as well as with women's organizations which resulted in an agreement that counseling and assistance will be provided by the servant. The results of the implementation of community service provide a positive value for UMK entrepreneurs with very satisfying indicators of success. Public information about brand rights was received enthusiastically by the community and provided a great motivation to increase industrial business skills so that the turnover can increase even more.